2020
DOI: 10.1007/s11356-020-09052-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation and secondary formation of size-segregated aerosol water-soluble inorganic ions in a coast megacity of North China Plain

Abstract: The aerosol samples of water-soluble inorganic ions (WSIs), including SO 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Therefore, the calculated sea salt proportion above was overestimated. However, it can be confirmed that the sea-sourced aerosols made up only a small fraction of the total aerosol particles in autumn, which is consistent with the results of previous studies conducted in the coastal city of Tianjin and Qingdao (Dong et al, 2023;Yao et al, 2020;Zhang, Yang, et al, 2021). In addition, the relative proportion of non-sea-sourced Cl À in this study was lower than that of non-sea-sourced SO 4 2À , suggesting that there might be some ageing process of sea salt, leading to the deficit of Cl À in sea spray aerosols.…”
Section: Contribution Of Marine Aerosols To Particlessupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the calculated sea salt proportion above was overestimated. However, it can be confirmed that the sea-sourced aerosols made up only a small fraction of the total aerosol particles in autumn, which is consistent with the results of previous studies conducted in the coastal city of Tianjin and Qingdao (Dong et al, 2023;Yao et al, 2020;Zhang, Yang, et al, 2021). In addition, the relative proportion of non-sea-sourced Cl À in this study was lower than that of non-sea-sourced SO 4 2À , suggesting that there might be some ageing process of sea salt, leading to the deficit of Cl À in sea spray aerosols.…”
Section: Contribution Of Marine Aerosols To Particlessupporting
confidence: 91%
“…SOR and NOR can be used to indicate the secondary transformation process (Ma et al, 2017). Higher values are always accompanied by a higher degree of SIA formation in the atmosphere (Yao et al, 2020). The details of the calculation are as follows: 3 | RESULTS It should be mentioned that there was a light snow on 6 November 2021.…”
Section: Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, nitrate and chloride may predominantly exist in the fine mode in winter and the coarse mode (>2 μm) in fall in coastal areas (Zhou et al., 2020). During the severe winter‐haze episodes, enhanced coarse‐mode mass concentration of sulfate was observed (Li et al., 2013) and the mode size of mass distributions of secondary inorganic aerosol (SIA, including sulfate, nitrate, and ammonium) could shift from 0.4 μm to >1 μm in northern China (Yao et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Primary particulate matter is usually produced by direct emissions of pollutant sources, such as soil dust from the ground, roads, and construction sites, biomass burning, and sea salt particles transported from the ocean. The secondary particulate matter is generally formed by the oxidation reaction of SO 2 (sulfur dioxide), NO X (nitrogen dioxide), NH 3 (ammonia) , and other gases (Yao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%